The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1108/bfj-01-2019-0070
|View full text |Cite
|
Sign up to set email alerts
|

The development of short food supply chain for locally produced honey

Abstract: Purpose The development of the short food supply chain (SFSC) is one of the issues of the current agri-food systems. Consumers are re-connecting the food they eat with the farming process and are increasingly asking for fresh, seasonal and traceable food products from known producer source. The purpose of this paper is to analyse consumers’ opinions towards the SFSC and willingness to pay (WTP) for local honeys in Mar del Plata, Argentina before and after a hedonic evaluation test. Design/methodology/approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Our results can be compared with the consumer study of Sama et al (2019) who showed that the utility of the Spanish consumer increased when the honey was produced in Spain (regional/local) compared to honey that came from outside of Europe (e.g., China, America). The origin of honey was also an important attribute that determined its quality, according to the results of previous studies (Batt & Liu, 2012; Bissinger & Herrmann, 2021; Bissinger et al, 2019; Blanc et al, 2021; Brun et al, 2020; Cosmina et al, 2016; Jensen & Mørkbak, 2013; Kallas et al, 2017; Kos‐Skubic et al, 2017; Oravecz et al, 2020; Pocol & Bolboacă, 2013; Ribeiro et al, 2019; Šánová et al, 2017; Vapa‐Tankosić et al, 2020; Wu et al, 2015; Zulail et al, 2014). Of special interest was the fact that honey coming from the EU generated a slightly higher implicit price over honey produced in Spain.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our results can be compared with the consumer study of Sama et al (2019) who showed that the utility of the Spanish consumer increased when the honey was produced in Spain (regional/local) compared to honey that came from outside of Europe (e.g., China, America). The origin of honey was also an important attribute that determined its quality, according to the results of previous studies (Batt & Liu, 2012; Bissinger & Herrmann, 2021; Bissinger et al, 2019; Blanc et al, 2021; Brun et al, 2020; Cosmina et al, 2016; Jensen & Mørkbak, 2013; Kallas et al, 2017; Kos‐Skubic et al, 2017; Oravecz et al, 2020; Pocol & Bolboacă, 2013; Ribeiro et al, 2019; Šánová et al, 2017; Vapa‐Tankosić et al, 2020; Wu et al, 2015; Zulail et al, 2014). Of special interest was the fact that honey coming from the EU generated a slightly higher implicit price over honey produced in Spain.…”
Section: Discussionmentioning
confidence: 86%
“…From a consumer's point of view, previous research from the last 11 years suggests that various honey characteristics affect the decision to purchase and consumers' WTP (see the detailed review on honey consumer studies from 2010 and onwards in Appendix , Table A1). Recent, consumer studies show that honey produced in local origins affect preferences and the WTP of Danish (Jensen & Mørkbak, 2013), Italian (Blanc et al, 2021; Brun et al, 2020; Cosmina et al, 2016), German (Bissinger & Herrmann, 2021; Bissinger et al, 2019), Romanian (Pocol & Bolboacă, 2013), Slovenian (Kos‐Skubic et al, 2017), Serbian (Vapa‐Tankosić et al, 2020), Hungarian (Oravecz et al, 2020), Portuguese (Ribeiro et al, 2019), Argentinian (Kallas et al, 2017), American (Wu et al, 2015), Saudi Arabian (Zulail et al, 2014), and Australian (Batt & Liu, 2012) consumers. Besides origin, consumers in Italy and Slovenia attach a great value to honey with the European PDO quality certification (Di Vita et al, 2021; Kos‐Skubic et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The short food supply chain enables consumers to better understand the situation of food and food producers. As such, purchasing intentions of consumers are likely to improve because they are more convinced that food is produced more safely (Kallas et al , 2019). Customers can purchase food directly from the manufacturer is believed to improve communication, build trust and reduce uncertainty in quality attributes (Cappelli and Cini, 2020; Kallas et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As such, purchasing intentions of consumers are likely to improve because they are more convinced that food is produced more safely (Kallas et al , 2019). Customers can purchase food directly from the manufacturer is believed to improve communication, build trust and reduce uncertainty in quality attributes (Cappelli and Cini, 2020; Kallas et al , 2019). In this context, it is important to analyze the moderating role of consumers’ SFSCP in enhancing consumers’ PI-behavior gap.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most scientific studies report the prevalence of honey adulteration and focus on the latest most advanced honey authenticity detection method (Fakhlaei et al, 2020;Se et al, 2019;Soares et al, 2017). From a commercial standpoint, there is an abundance of studies assessing consumers' honey preferences and honey's criteria affecting their purchase decision (Batt & Liu, 2012;Blanc et al, 2021;Kallas et al, 2019;Murphy et al, 2000). However, little is known about consumers' understanding and awareness about the issue of fraudulent honey, as such, insight on the level of consumer awareness about fraudulent honey and the effect of awareness on their intention to purchase fraudulent honey warrant further investigation.…”
Section: Problem Statementmentioning
confidence: 99%